Optimal controller design for autonomous quadrotor landing on moving platform - Cengiz, Said Kemal; Ucun, Levent (ELSEVIER, 2022)
Different aviation applications gain importance rapidly nowadays where the autonomy of Unmanned Aerial Vehicles (UAVs) become essential in many different engineering fields. In this study, detailed research is carried out for different control methods that can be implemented to a quadrotor which is defined as a popular example of UAVs. In order to fulfill the scenario of this study, two different optimal controllers based on Linear Quadratic Gaussian (LQG) and Model Predictive Control (MPC) algorithms, are designed for a quadrotor that autonomously follows a moving platform from an arbitrary initial position and performs landing on the platform with high precision. Accordingly, the results of these controllers are presented comparatively via the simulation studies and the necessary analysis is given in order to show the efficiency of proposed controllers for the landing mission on a moving platform.
Keywords: Quadrotor flight control; Optimal controller design; Linear quadratic gaussian; Model predictive control; Autonomous flight; Computer Science